Some problems of learning the language of literary work - Kadirbaevna, Erjanova Dilfuza; Pakhratdinov, K. (International Journal of Psychosocial Rehabilitation, 2020)
Learning the language of literary work is very important for linguistics, any literary work describes the time reflection of the common language, its condition. The language of the literary work depends on the norms of literary language, its phonetic and grammatical laws, but it differs from the literary norms with its emotional-expressivity and its stylistic devices, it shows the poet’s own skill on choosing and using the words. When the language of the literary work is learned, it’s necessary to define how the writer or poet used the stylistic devices in the work, how he used the words to create the artistic character, his own skill on using the words and style. At that time the writer’s language features, his own style, the language features of the literary work will be discovered. In the article the lingua-poetic analysis of the language of the literary work is analyzed overall and discovered in the basis of the words with a portable meaning, synonyms, antonyms, homonyms, assimilated words, phraseologisms, proverbs, focus words and phonetic circumstances in the language of poems by the Karakalpak national poet I.Yusupov.